(untitled) (Al-Nahrain Journal of Science, 2018)
Study the effect of time, temperature & storage on the microbial population for regional produced samples of bottled water( healthy drink water) and for another imported sample, depending on studies done by several international organizations in other countries to determine the effect of mentioned conditions above on the maintainace of purity of bottled water in order to find the degree of resemblance between the results of these studies & results of same experiment during the production & marketing of bottled water in our environmental & life-style circumstances of our country.The following study found that the microbial growth rate was increase with the using time of these samples in 24,48 hr. and the no. of growing microorganisms in the samples stored at 4C (at refrigerator) were less than the no. of microorganisms in other samples that stored in room temperature (25-27)C during use.